2018
DOI: 10.3390/cryst8080315
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Switching Current Data during Polarization Reversal in KTP Single Crystals with Surface Dielectric Layer

Abstract: Studies of polarization reversal processes in potassium titanyl phosphate (KTiOPO 4 , KTP) single crystals with surface dielectric layer are important due to their potential applications as the basis of bottom-up technology for creation of periodically poled nonlinear-optical crystals. We present the results of switching currents analysis accompanied by in situ visualization of domain kinetics during polarization reversal in KTP with 3 m-thick photoresist dielectric layer. Qualitative change of the switching c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The in situ imaging of the domain kinetics was realized for the first time by a complicated experimental method of digital holography . Recently, the in situ optical imaging with high temporal resolution accompanied by simultaneous recording of the switching current has been applied for a detailed study of the domain evolution in KTP. It has been shown that the polygonal isolated domains in KTP have symmetrically nonequivalent slow, fast, and super-fast domain walls, which differ in velocity by several orders of magnitude. , …”
Section: Introductionmentioning
confidence: 99%
“…The in situ imaging of the domain kinetics was realized for the first time by a complicated experimental method of digital holography . Recently, the in situ optical imaging with high temporal resolution accompanied by simultaneous recording of the switching current has been applied for a detailed study of the domain evolution in KTP. It has been shown that the polygonal isolated domains in KTP have symmetrically nonequivalent slow, fast, and super-fast domain walls, which differ in velocity by several orders of magnitude. , …”
Section: Introductionmentioning
confidence: 99%